PENGARUH STRUKTUR MODAL, NET PROFIT MARGIN, EARNING PER SHARE DAN FIRM SIZE TERHADAP PRICE BOOK VALUE PADA PERUSAHAAN SUB SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI INDONESIAN STOCK EXCHANGE PADA TAHUN 2014-2017 - Pangaribuan, L.R.Maria; Sihombing, Yeni Rafita; Hasugian, Siska Satriani; Purba, Devi Lesnawati (Yayasan Akrab Pekanbaru, 2019)
The purpose of the research is to explain and to prove the significan influence of partial between capitality structure , net profit margin, earning per share, and firm size to price book value (property business and real estate registered Indonesian stock exchange in 2014-2017) independent variable are debt to equity ratio (DER) is a calculation of capitality structure and net profit margin, earning per share and firm size while the dependent variable are price book value (PBV) which is a calculation of the value of the company. The sampling technique of research is purposive sampling has result 28 companies as research sample 48 companies. The data analysis method used the multiple linear. The research result concluded there was influence, capirality structure, net profit margin, earning per share and firm size,